2020
DOI: 10.1021/acs.biomac.0c00127
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose–Chitosan Paper with Antimicrobial and Antioxidant Activities

Abstract: The production of paper based bacterial cellulose-chitosan (BC-Ch) nanocomposites was accomplished following two different approaches. In the first, BC paper sheets were produced and then immersed in an aqueous solution of chitosan (BC-ChI); in the second, BC pulp was impregnated with chitosan prior to the production of the paper sheets (BC-ChM). BC-Ch nanocomposites were investigated in terms of physical characteristics, antimicrobial and antioxidant properties, and ability to inhibit the formation of biofilm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 46 publications
5
51
0
Order By: Relevance
“…Fernandes et al [ 39 ] also reported that increased bacterial cellulose contents promoted crystallization of chitosan chains as observed in the diffractograms of water soluble chitosan/bacterial cellulose nanocomposite films. The strength of the crystalline peak increased with increased CNFs content which was due to the high biocompatibility between chitosan and cellulose [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fernandes et al [ 39 ] also reported that increased bacterial cellulose contents promoted crystallization of chitosan chains as observed in the diffractograms of water soluble chitosan/bacterial cellulose nanocomposite films. The strength of the crystalline peak increased with increased CNFs content which was due to the high biocompatibility between chitosan and cellulose [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This structure possesses exclusive features, such as high mechanical strength, water-holding capacity, dimensional stability, crystallinity, biocompatibility, and biodegradability (Picheth et al, 2017). Given these features, numerous applications of BNC have been studied: in the biomedical field as a wound dressing, for tissue regeneration/substitution, drug delivery systems, biosensors and cancer diagnosis; in the textile and paper industries for fiber composites and coatings; in the food and cosmetic industries as an emulsifier and viscosifier (Klemm et al, 2005;Chawla et al, 2009;Müller et al, 2013;Nimeskern et al, 2013;Lee et al, 2014;Shi et al, 2014;Rajwade et al, 2015;Ul-Islam et al, 2019;Amorim et al, 2020;Anton-Sales et al, 2020;Cabañas-Romero et al, 2020;Farooq et al, 2020;Liu et al, 2020;Nanollose, 2020). The main application is still as a food item known as nata de coco, mostly produced and consumed in Asian countries (Dourado et al, 2016a).…”
Section: Bacterial Nanocellulosementioning
confidence: 99%
“…Combination of BNC with other polymers was also used to provide antimicrobial properties. Cabañas-Romero et al [ 114 ] produced composites by immersing bacterial nanocellulose in a chitosan solution. The obtained composite material not only exhibited antimicrobial activity against Gram-positive and Gram-negative bacteria, but also showed antioxidant activity and good mechanical properties [ 114 ].…”
Section: Bnc In Food Packaging Applicationsmentioning
confidence: 99%
“…Cabañas-Romero et al [ 114 ] produced composites by immersing bacterial nanocellulose in a chitosan solution. The obtained composite material not only exhibited antimicrobial activity against Gram-positive and Gram-negative bacteria, but also showed antioxidant activity and good mechanical properties [ 114 ]. Another approach to impart bactericidal features to BNC matrices was the incorporation of metal ions and oxides (e.g., silver, gold, copper, platinum, ZnO, TiO 2 , MgO) [ 90 ].…”
Section: Bnc In Food Packaging Applicationsmentioning
confidence: 99%